Improving Summarization Performance by Sentence Compression - A Pilot Study - Lin, Chin-Yew (The Sixth International Workshop on Information Retrieval with Asian Language (IRAL 2003), 2003)
In this paper we study the effectiveness of applying sentence compression on an extraction based multi-document summarization system. Our results show that pure syntactic-based compression does not improve system performance. Topic signature-based reranking of compressed sentences does not help much either. However reranking using an oracle showed a significant improvement remains possible.